Feasibility of planctomycetes as a nutritional or supplementary food source for Daphnia spp - Antunes S.C. (2016)
Daphnia magna is widely used as a standard organism in ecotoxicology assays. It plays a key role in energy transfer in freshwater food webs as a primary consumer, grazing on microalgae, yeast and bacteria. Daphnids are commonly reared in the laboratory using microalgae cultures but alternative or complementary sources are important to reduce the dependency on a single food source. The role played in nature by planctomycetes as a food source for other higher trophic levels is still unknown. In this study, we aimed to evaluate the potential of Rhodopirellula rubra strain LF2 as a nutritional or a supplementary food source for D. magna and Daphnia longispina. Life-history assays were conducted with daphnids fed with R. rubra in exponential and stationary growth phases, in three concentrations. Additionally, its adequacy as a supplement to the microalga Raphidocelis subcapitata was tested. In general, both daphnids showed impairment in all the parameters evaluated, especially when fed with R. rubra. However, when daphnids were fed with the two food sources, no changes were recorded for the rate of population increase. At the tested concentrations, R. rubra was not a good alternative food source in the daphnid diet. © EDP Sciences, 2016.